Penerapan Karyawan Berprestasi dengan Metode Profile Matching Pada PT. Intisel Prodaktifakom Semarang - Santoso, Bagas; al-Amin, Imam Husni (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2023)
The process of selecting high-performing employees at PT. Intisel Prodaktifakom Semarang still relies heavily on hardcopy forms and decisions made by a single party, resulting in an inaccurate process. The selection of outstanding employees is still done manually, leading to an ineffective search process and difficulties in decision-making and obtaining hardcopy data. In the conducted research, several criteria are used for decision-making, namely Work Target Aspect, Work Behavior Aspect, and Work Discipline Aspect. Therefore, a decision support system greatly aids the company in decision-making, analyzed using the Profile Matching method. Implementing the Profile Matching method at PT. Intisel Prodaktifakom Semarang makes it easier to make decisions in selecting high-performing employees based on their capabilities. This research aims to determine the ranking and weightage of criteria in the selection of outstanding employees at PT. Intisel Prodaktifakom Semarang.